CsPbI3 nanorods as the interfacial layer for high-performance, all-solution-processed self-powered photodetectors. (10th June 2021) - Saleem, Muhammad Imran; Yang, Shangyi; Batool, Attia; Sulaman, Muhammad; Veeramalai, Chandrasekar Perumal; Jiang, Yurong; Tang, Yi; Cui, Yanyan; Tang, Libin; Zou, Bingsuo
Graphical abstract: Abstract: Heterojunction is regarded as a crucial step toward realizing high-performance devices, particularly, forming gradient energy band between heterojunctions benefits self-powered photodetectors. Therefore, in this paper, the synthesis of CsPbI3 nanorods (NRs) and its application as the interfacial layer in high-performance, all-solution-processed self-powered photodetectors are presented. For the bilayer photodetector ITO/ZnO(100 nm)/PbS-TBAI(150 nm)/Au, a responsivity of 3.6 A/W with a specific detectivity of 9.8 × 10 12 Jones was obtained under 0.1 mW/cm 2 white light illumination at zero bias (i.e. in self-powered mode). Meanwhile, the photocurrent was enhanced to an On/Off current ratio of 10 5 at zero bias with an open circuit voltage of 0.53 V for trilayer photodetector ITO/ZnO(100 nm)/PbS-TBAI(150 nm)/CsPbI3 (250 nm)/Au, in which the CsPbI3 NRs layer works as the interfacial layer. As a result, a specific detectivity of 4.5 × 10 13 Jones with a responsivity of 11.12 A/W was obtained under 0.1 mW/cm 2 white light illumination, as well as the rising/decaying time of 0.57 s/0.41 s with excellent stability and reproducibility upto four weeks in air. The enhanced-performance is ascribed to the mismatch bandgap between PbS-TBAI/CsPbI3 interface, which can suppress the carrier recombination and provide efficient transport passages for charge carriers. Thus, it provides a feasible and efficient method for high-performance photodetectors.